Respostas
respondido por:
1
Sendo sen^2(a)+cos^2(a)=1 e substituindo na equação obteremos!
-5cos(a)+4=0
cos(a)=-4/5
Substituindo cos(a) na equação fundamental
16/25+sen^2(a)=1
Sen(a)=raiz quadrada de 1-16/25
Sen(a)=3/5
Sendo tg(a) = sen(a)/cos(a)
Tg(a)=3/5.-5/4
Tg(a)=-15/20
Tg(a)=3/4
-5cos(a)+4=0
cos(a)=-4/5
Substituindo cos(a) na equação fundamental
16/25+sen^2(a)=1
Sen(a)=raiz quadrada de 1-16/25
Sen(a)=3/5
Sendo tg(a) = sen(a)/cos(a)
Tg(a)=3/5.-5/4
Tg(a)=-15/20
Tg(a)=3/4
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás